ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PT METRODATA ELECTRONICS, Tbk DAN PT DYVIACOM INTRABUMI, Tbk DENGAN PENDEKATAN ECONOMIC VALUE ADDED - Beny, Beny (MABIS, 2012)
The research is done to the PT Metrodata Electronics, Tbk and PT Dyviacom Intrabumi, Tbk those listed on Bursa Efek Jakarta in order to measure the financial performance of the companies. The audited financial statement that used to research the performance is from 2008 until 2011, Economic Value Added method is used to analyze the performance.